Use of crude plant extract of Adhatodavasica as insecticides againstBemisiatabaci - Muter , Haifa N.; Mohammed , Ali S. (Iraqi Journal of Science, 2022)
The present study evaluates the insecticidal activity of (Acetone, 80% Methanol and water) crude leaf extract of AdhatodavasicaagainstBemisiatabaci. The extracts of (Acetone, Methanol 80%) showed 100, 86.6% mortality of nymphsBemisiatabaci at 5% concentration. Then the extracts of (Acetone, Methanol 80%) showed 100, 90% mortality of pupaBemisiatabaci at 5% concentration. Phytochemical screening revealed the presence of (Flavones, Volatiles oils, Tannins, Saponines, Glycosides, Alkaloids,Resins and Terpenoids)in methanol80% crude extract. It can be concluded that the acetone and methanol crude leaf extract of A. vasicaNees can cause mortality in (nymphs, pupa) Bemisiatabaci, so it can be used asinsecticides.